Molecular cloning and expression profiles of an insulin-like growth factor binding protein IGFBP5 in the pearl oyster, Pinctada fucata. Issue 1 (1st January 2018) - Fan, Sigang; Wang, Zhenzhen; Yu, Dahui; Xu, Youhou
ABSTRACT: The insulin-like growth factor binding protein (IGFBP) family participates in transportation, localization, and biological regulation of insulin-like growth factors (IGFs). In the present study, IGFBP5 gene from the Pinctada fucata ( PfIGFBP5 ) was cloned and characterized. The full-length cDNA sequence (1319 bp) contained an open reading frame of 399 bp encoding a predicted protein of 132 amino acids. The amino acid sequence of PfIGFBP5 included an IGF binding domain and multiple cysteine residues. The genomic sequence of PfIGFBP5 consisted of three exons and two introns. PfIGFBP5 was found to be expressed in all tissues and developmental stages investigated, although the expression level was significantly higher in the pearl sac and in trochophore larvae than in other tissues or developmental stages ( P < 0.05 ). Expression of PfIGFBP5 was induced by notching the oyster shell margin; the gene was mainly expressed in the outer epithelium of the mantle, and to a lesser extent in the whole pearl sac, including connective tissues. These findings suggest that PfIGFBP5 is very likely to be involved in modulating biomineralization in the mantle and pearl sac of P. fucata since they are the main organs for shell or pearl formation.